Tawhidi Scientific Research Program (Tsrp): Islamic Socio-Scientific Inquiry - Masudul Alam Choudury (Indonesian Journal of Islamic Economics and Finance)
A process model is derived from the Tasbih-Shura nature of the Shuratic process (discursive process). The Tasbih-Shura dynamics is consultative and participatory, hence discursive in the light of the Qur'an. The imminent Shuratic process is thus a methodology associated with the meaning of the embryonic Shura as a discursive medium that spans across all domains of socio-scientific inquiry. The existence of such inherent and pervasive discursive dynamics is to be found in all realms of the natural and human order; in the abstraction of the seen and unseen worlds, about which the Qur’an speaks. The latter kind of world-system may be temporally revealed or may remain permanently hidden. Yet in all conditions, the monotheistic law makes all such domains profoundly interactive and integrative in the sense of knowledge-inducing human discursive experience and the participative complementary nature of the world-system. This kind of exercising effort (Ijtihad) is used to discover the conscious learning nature of all things (Tasbih).